Developmental programming of hypothalamic neuronal circuits: impact on energy balance control - Gali Ramamoorthy, Thanuja; Begum, Ghazala; Harno, Erika; White, Anne (Frontiers in Neuroscience, 2015)
The prevalence of obesity in adults and children has increased globally at an alarming rate. Mounting evidence from both epidemiological studies and animal models indicates that adult obesity and associated metabolic disorders can be programmed by intrauterine and early postnatal environment- a phenomenon known as “fetal programming of adult disease”. Data from nutritional intervention studies in animals including maternal under- and over-nutrition support the developmental origins of obesity and metabolic syndrome. The hypothalamic neuronal circuits located in the arcuate nucleus controlling appetite and energy expenditure are set early in life and are perturbed by maternal nutritional insults. In this review, we focus on the effects of maternal nutrition in programming permanent changes in these hypothalamic circuits, with experimental evidence from animal models of maternal under- and over-nutrition. We discuss the epigenetic modifications which regulate hypothalamic gene expression as potential molecular mechanisms linking maternal diet during pregnancy to the offspring’s risk of obesity at a later age. Understanding these mechanisms in key metabolic genes may provide insights into the development of preventative intervention strategies.